Research on multi-tenant data partition mechanism for SaaS application based on shared schema - Xiao-na LI; Qing-zhong LI; Lan-ju KONG; Cheng PANG (Tongxin xuebao)
In SaaS model,the multi-tenant data using shared schema partitioned in multiple nodes of the cloud environment was put forward in advance.Based on this,a data partition model and algorithm for multi-tenants to support SaaS application was proposed.Through comparsion with many data partition technology and cloud database solutions mainly for analysis application and lack of transaction support,the theoretical analysis and experimental results reveal that the proposed data partition mechanism can effectively realize the dynamic scalability of the system in cloud environment,at the same time to minimize the cost of the distributed transaction.